ERRORS MADE BY THE EIGHTH GRADE STUDENTS OF SMP NEGERI 31 MEDAN IN WRITING ENGLISH COMPOSITIONS - Waruwu, Idam Putriyani; Sembiring, Novalina; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
Writing English composition is more complicated than Indonesian compositions. Therefore, students often make errors in writing English compositions. This study aims at finding out the errors made by the eighth grade students of SMP Negeri 31 Medan in writing English composition and to find out the causes of those errors. The population of this study is the eighth grade students of SMP Negeri 31 Medan in Academic Year 2017/2018. The sample is class VIII-A with 30 students. The instrument for collecting data were the students’ English compositions and the questionnaires. The result from the students’ English compositions showed that third singular verb in morphological errors is the highest error made by the students (55,10%), followed by errors in definite article (20,40%), errors in Possesive Case (12,24%), errors in Comparative Adjective or Adverb (12,24%); the errors of syntactical errors in Verb or Verb Phrase (50%), Errors in Noun or Noun Phrase (25%) and Errors in Word order (25%). It means that the eighth grade students of SMP Negeri 31 Medan are poor in writing English compositions. While the result of the questionnaires showed that there are several reasons that cause students error. The three highest reasons are the students do not have a sufficcient vocabulary, students do not comprehend how to use the third singular verbs, article and possesive and the English teacher never asked the students to write English compositions. Thus, the students are suggested to study and more about writing English compositions and to do exercises about it. The teacher should give more writing practice to the students.